2017
DOI: 10.4103/0973-6247.200775
|View full text |Cite
|
Sign up to set email alerts
|

Snake in the grass: A case report of transfusion reactions due to contaminated donor arm disinfectant

Abstract: Bacterial contamination of blood components remains an on-going challenge. In the majority of cases, organisms contaminating the blood components are a part of normal skin flora. Here, we report a case of bacterial contamination of blood units through contaminated donor arm disinfectant. There was a series of reactions due to random donor platelet (RDP) transfusion. The patients had features of septic transfusion reactions. On root cause analysis, spirit swabs used for disinfection of donors’ arm were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…These two bacteria types are responsible for the increased incidence of severe sepsis and septic shock as reported by (Babu M, et al) 13 The isolated bacteria in this study, as found in other research were part of the skin flora. 3 Similar bacteria on the antecubital fossa of potential blood donors were found in an early study by our group (Article in press). With the exception of Staphylococcus aureus which can causing a serious problems, 14 most of the time, these bacterial species found in this study are generally associated with non-fatal septic transfusion reactions.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…These two bacteria types are responsible for the increased incidence of severe sepsis and septic shock as reported by (Babu M, et al) 13 The isolated bacteria in this study, as found in other research were part of the skin flora. 3 Similar bacteria on the antecubital fossa of potential blood donors were found in an early study by our group (Article in press). With the exception of Staphylococcus aureus which can causing a serious problems, 14 most of the time, these bacterial species found in this study are generally associated with non-fatal septic transfusion reactions.…”
Section: Discussionsupporting
confidence: 75%
“…At the CHU laboratory, every PCs are disinfected for at least one minute with a disinfectant (70% concentrated Alcohol), 3 the bacterial culture was done aseptically from PCs samples following the World Health Organization (WHO) recommendations. 11 The bacterial cultures broths were incubated in aerobic atmosphere at 37°C for 7 days and were daily controlled for any possible signs of bacterial growth (turbidity, color, voile…).…”
Section: Bacteriological Detection Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The uppermost layer and deeper layers of the skin harbour many resident and transient bacteria [24]. Apart from causing diseases when transmitted from one person to another, they run the risk of contaminating blood products if proper cleaning of the antecubital fossa is not carried out [25]. Cleaning the skin with soap and water is more effective than washing the skin with just water or no hand washing at all [26].…”
Section: The Cleaning Techniquementioning
confidence: 99%
“…A Blood &Transplant study conducted by NHS revealed reduction in contamination of blood products by 57% using improved disinfection strategies [13] .…”
Section: Introductionmentioning
confidence: 99%